2017
DOI: 10.4155/fmc-2017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Synthetic Thymoquinone Analogs: New Prototypes as Potential Antihyperlipidemics in Irradiated Rats

Abstract: TQ derivatives (4-7), could be considered as promising agents in pathologies implicating impaired lipid metabolism, preclinical evaluation is warranted. [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These results are consistent with those in previous studies of irradiation consequences. 11 Afonso et al 48 found that the reduction in LCAT activity led to the free accumulation of cholesterol and excess plasma lipoprotein as LCAT is the essential enzyme for esterification and trans-esterification in the cholesterol process. It has been confirmed that PS therapy normalizes to a large extent the pathological changes in tissues of dyslipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those in previous studies of irradiation consequences. 11 Afonso et al 48 found that the reduction in LCAT activity led to the free accumulation of cholesterol and excess plasma lipoprotein as LCAT is the essential enzyme for esterification and trans-esterification in the cholesterol process. It has been confirmed that PS therapy normalizes to a large extent the pathological changes in tissues of dyslipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The second is acyl-CoA cholesterol acyltransferase (ACAT) and lecithin cholesterol acyltransferase (LCAT), and, thirdly, cholesterol 7-hydroxylase, which is the rate-limiting enzyme in cholesterol catabolism to bile acid low-density lipoproteins (LDL) receptor, high-density lipoproteins (HDL) receptor, and scavenger receptor class B type 1 (SRB-1). 11,12 In correlation with the above, Meneses et al 13 stated that PON-1/ ARE-1 possesses antioxidant properties and is closely associated with HDLs, which detoxify lipid peroxides and protect LDLs from oxidation. Besides, Phua et al 14 noted that peroxisome proliferator-activated receptor (PPAR) controls adipocyte differentiation, glucose metabolism, and lipid homeostasis.…”
mentioning
confidence: 94%
“…PQTU was prepared by a one-pot method with benzoquinone and thiourea as precursors. Benzoquinone (324 mg, 3 mmol) and thiourea (76 mg, 1 mmol) were added to 20 mL of ethanol and were heated to reflux for 9 h under an air atmosphere. After cooling to room temperature, the reaction mixture was filtered.…”
Section: Methodsmentioning
confidence: 99%
“…Disease Models References sulfur-containing TQ-analogs radiation-induced dyslipidemia in rats [28] nitrogen-substituted TQ analogues human ovarian cancer cell lines [29] 3aminothymoquino ne antifungal effect against Candida albicans, Saccharomyces cerevisiae and Aspergillus brasiliensis [30] By studying TQ and human serum albumin (HSA) interactions, results showed that the association of TQ with HSA did not affect the secondary structure of HSA. Moreover, the HSA/TQ thermodynamic analysis reported that the binding process occurred spontaneously, and the hydrophobic interactions were the principal intermolecular forces that stabilize the complex [31].…”
Section: Typementioning
confidence: 99%